Obstacles of Indonesia Language Tearchers in the Implementation of the Independent Learning Curriculum at SMPN 18 Bengkulu City - Ikhsan Achmadi Putra; Yanti Paulina; Tri Dina Ariyanti; Hasmi Suyuthi (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The Merdeka curriculum focuses on diverse intracurricular learning and on developing students' competencies and character so that it is more flexible and gives students enough time to learn concepts and strengthen their skills as a whole. The independent curriculum will begin in stages at SMPN 18 Bengkulu City in 2021. With the change in the curriculum in implementing it, of course there are obstacles experienced by schools and teachers at SMPN 18 Bengkulu City, especially Indonesian language teachers. Therefore, this study aims to find out what are the obstacles faced by Indonesian teachers in the implementation of the Independent Learning Curriculum in Indonesian language subjects at SMPN 18 Bengkulu City. This research is qualitative descriptive. The data collection process uses observation, interview, and documentation techniques. The data analysis used by the researcher is data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the independent curriculum at SMPN 18 Bengkulu City began in 2021. In this study, Indonesian teachers faced three obstacles: teaching module planning, classroom learning methods, student heterogeneity, differences in talents and interests that make determining differentiated learning that suits students' needs, and determining assessments that are in accordance with the material. Plus, there are many types and forms of assessment in project learning, which makes it difficult for teachers to define project-based learning.